2022
DOI: 10.1126/sciadv.abm6756
|View full text |Cite
|
Sign up to set email alerts
|

Human organ rejuvenation by VEGF-A: Lessons from the skin

Abstract: Transplanting aged human skin onto young SCID/beige mice morphologically rejuvenates the xenotransplants. This is accompanied by angiogenesis, epidermal repigmentation, and substantial improvements in key aging-associated biomarkers, including ß-galactosidase, p16 ink4a , SIRT1, PGC1α, collagen 17A, and MMP1. Angiogenesis- and hypoxia-related pathways, namely, vascular endothelial growth factor A (VEGF-A) and HIF1A, are most up-regulated in rejuvenated human skin. This rejuvenation casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 107 publications
2
40
0
Order By: Relevance
“…Analysis of Sirt‐1 expression revealed a significant down‐regulation at the protein level in the epidermis at Day 3 of hSOC compared to Day 0 (Figure 1E,E′). This is perfectly in line with the recognized decline in Sirt‐1 during both intrinsic and extrinsic skin ageing 7,45 . Given that a reduction in mitochondrial function and activity is closely linked to tissue ageing, 14,46 it is important to note that we also found a significantly reduced epidermal protein expression of mitochondrially encoded cytochrome c oxidase I (Figure S1B,B′) and decreased respiratory chain complex II/IV activity after 3 days of hSOC (Figure S1C,C′).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Analysis of Sirt‐1 expression revealed a significant down‐regulation at the protein level in the epidermis at Day 3 of hSOC compared to Day 0 (Figure 1E,E′). This is perfectly in line with the recognized decline in Sirt‐1 during both intrinsic and extrinsic skin ageing 7,45 . Given that a reduction in mitochondrial function and activity is closely linked to tissue ageing, 14,46 it is important to note that we also found a significantly reduced epidermal protein expression of mitochondrially encoded cytochrome c oxidase I (Figure S1B,B′) and decreased respiratory chain complex II/IV activity after 3 days of hSOC (Figure S1C,C′).…”
Section: Resultssupporting
confidence: 85%
“…Additionally, our pilot study provides the first persuasive evidence that both, systemic caffeine and the topically applied, TRPM5‐targeting natural pheromone, DMP, significantly retard human skin ageing ex vivo. This opens intriguing new perspectives for dissecting the molecular controls that drive human skin ageing/senescence, for cosmetic and pharmacological research on skin senolytics, which can be followed up in vivo by studying aged human skin xenotransplants on SCID beige mice, 7 and for human ageing research in general. Further, the simple organ culture system reported here invites additional applications, such as assessing how cytostatic and/or genotoxic drugs impact on the quality, dynamics and speed of spontaneous human skin ageing ex vivo as well as on immunosenescence‐associated biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term inhibition of VEGF-A may lead to undesired age-promoting effects 64,65 and, therefore, anti-VEGF-A therapy for the management of psoriasis may best be administered as repetitive pulse therapy. In addition, nanotechnology-based angiogenesistargeting strategies could be used to minimise the potential systemic complications associated with tissue ageing effects of blocking VEGF-A, as these can also F I G U R E 4 Blood vessel area downregulation correlated with the levels of VEGF-A in plasma and VEGF-A production in psoriasis plaque skin (a) The median level of VEGF-A in plasma of patients with psoriasis and healthy volunteers was 25.38 (range 13-81) pg/ml and 14.13 (3-71) pg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term inhibition of VEGF‐A may lead to undesired age‐promoting effects 64,65 and, therefore, anti‐VEGF‐A therapy for the management of psoriasis may best be administered as repetitive pulse therapy. In addition, nanotechnology‐based angiogenesis‐targeting strategies could be used to minimise the potential systemic complications associated with tissue ageing effects of blocking VEGF‐A, as these can also lead to renal and cardiovascular impairment 66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified vascular endothelial growth factor (VEGF) as a major driver of human organ rejuvenation in vivo [ 35 ]. Specifically, VEGF-A in young mice has been reported to rejuvenate the aging skin phenotype via enhanced angiogenesis in human xenodermal grafts [ 36 ]. This study revealed no obvious rejuvenation effect in the control-treated group after transplantation.…”
Section: Discussionmentioning
confidence: 99%